2022
DOI: 10.1038/s41531-022-00363-2
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of gangliosides in four brain regions from Parkinson’s disease patients with a GBA mutation

Abstract: A number of genetic risk factors have been identified over the past decade for Parkinson’s Disease (PD), with variants in GBA prominent among them. GBA encodes the lysosomal enzyme that degrades the glycosphingolipid, glucosylceramide (GlcCer), with the activity of this enzyme defective in Gaucher disease. Based on the ill-defined relationship between glycosphingolipid metabolism and PD, we now analyze levels of various lipids by liquid chromatography/electrospray ionization-tandem mass spectrometry in four br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 47 publications
3
22
0
Order By: Relevance
“…In patients with PD, GCase deficiency specific to the SN was reported, 34 but in either putamen or cerebellum of patients with PD with or without GBA mutation(s), there were no or few changes in glucosylsphingosine, sphingomyelin, gangliosides (GM2, GM3), or total cholesterol. 8,39,40 In fact, other studies even reported reduced glycosphingolipids in brain regions with significant PD pathology (discussed in Lansbury 17 ) and compensatory upregulation of ceramide synthase-1 gene expression, 30 which would possibly increase overall sphingolipid recycling per time (flux). In PD, multiple glycosphingolipid abnormalities were observed in plasma independent of changes in GlcCer or GCase.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with PD, GCase deficiency specific to the SN was reported, 34 but in either putamen or cerebellum of patients with PD with or without GBA mutation(s), there were no or few changes in glucosylsphingosine, sphingomyelin, gangliosides (GM2, GM3), or total cholesterol. 8,39,40 In fact, other studies even reported reduced glycosphingolipids in brain regions with significant PD pathology (discussed in Lansbury 17 ) and compensatory upregulation of ceramide synthase-1 gene expression, 30 which would possibly increase overall sphingolipid recycling per time (flux). In PD, multiple glycosphingolipid abnormalities were observed in plasma independent of changes in GlcCer or GCase.…”
Section: Discussionmentioning
confidence: 99%
“…The PD patients were classi ed as IPD and most displayed characteristic Lewy body (LB) pathology, according to the case study data. For PD-GBA brains 13 , GBA1 mutations included, among others, patients with the N370S and the L444P mutations which are found at high levels in association with PD 3 . The same samples were used for a recent non-targeted lipidomics study, in which elevation of levels of gangliosides was detected in four brain regions 13 , although no signi cant changes were observed in levels of GlcCer.…”
Section: Methodsmentioning
confidence: 99%
“…A number of approaches have been used to attempt to delineate the mechanistic relationship between PD and GBA1 mutations, among them, high throughput omics [9][10][11][12] . Recently we used a unique tissue collection of brain tissues from idiopathic PD (IPD) and PD-GBA patients to perform a non-targeted lipidomics analysis of four different brain regions 13 , namely the striatum (STR), which is part of the nigrostriatal dopaminergic pathway, and also the occipital cortex (OCC), middle temporal gyrus (MTG) and cingulate gyrus (CG). No changes in levels of glucosylceramide (GlcCer), the substrate of GCase, were observed although levels of gangliosides (sialic acid-containing glycosphingolipids) were elevated in 3 of the 4 brain regions in such a way that suggests upregulation of the pathway of ganglioside metabolism rather than modulation of the activity of speci c enzymes in the pathway.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). However, these GCase activity and lipid changes have only been observed in certain regions, at certain ages, and have not been found consistently across cohorts [24][25][26][27] . Most previous studies have focused on either GCase activity or glycosphingolipid analyses; idiopathic or GBA1 PD, making it difficult to draw conclusions across studies.…”
Section: Introductionmentioning
confidence: 92%